The Effect of Using Augmented Reality-Based Android Applications in Practical Activities on Students' Science Process Skills - Akbar, Jakkub Saddam; Amalina, Ijtihadi Kamilia; Howan, Dian Herlinda Octorina; Djakariah, Djakariah; Aldresti, Fitri (Electronic Journal of Education, Social Economics and Technology, 2024)
This research aims to examine the effect of using an Android application based on Augmented Reality (AR) in practical activities on students' science process skills. The research used a pre-experimental design with a one-group pretest-posttest design involving 35 students at MAK Madani Manado. The research results show a significant increase in students' science process skills, which can be seen from the average pretest score of 52.48 and posttest of 86.69. This increase reflects the effectiveness of using AR-based applications in helping students improve their skills in observing, classifying, formulating hypotheses, designing experiments, processing data, and drawing conclusions. AR applications provide a more interactive learning experience by allowing students to visualize abstract concepts in a real way so that chemistry learning becomes more interesting and meaningful. These findings provide a positive contribution to the development of more innovative and contextual chemistry learning strategies, as well as offering solutions to overcome limited laboratory facilities in schools. The use of AR applications in chemistry learning also supports the creation of learning experiences that are relevant to learning needs in the digital era, thereby increasing student motivation and involvement in learning.